2020
DOI: 10.5620/eaht.2020025
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of melatonin on nickel-induced affective and cognitive disorders and oxidative damage in rats

Abstract: The present work is carried out to explore the neuroprotective potential of Melatonin(Mel), on Ni-induced neurobehavioral, biochemical and histological alterations in male and female rats. The rats were intraperitoneally administered by nickel chloride (NiCl2, 1 mg/kg) and Mel (4 mg/kg) for 60 days. A neurobehavioral assessment was performed. Biochemical determinations of oxidative stress (OS) levels, and histological analysis of hippocampal tissues were also performed. Results showed that Nickel (Ni) treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…46 Txnrd2 deletion leads to an increase in infarction size and apoptosis of cardiomyocytes and impairs postischemic functional recovery of the heart. 47 48,49 We performed the median lethal dose (LD 50 ) and concentration gradient pre-experiments (the concentrations of NiCl 2 solution were set at 8, 10, and 12 mg/kg; the concentrations of Mel solution were set at 2, 5, and 8 mg/kg) to determine the lowest concentration of NiCl 2 that could cause damage in mice and the maximum concentration of Mel that could treat for Ni without causing damage. All animals had free access to food and water for 21 days, and mice were then placed in clean containers and euthanized by slow infusion of carbon dioxide (CO 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…46 Txnrd2 deletion leads to an increase in infarction size and apoptosis of cardiomyocytes and impairs postischemic functional recovery of the heart. 47 48,49 We performed the median lethal dose (LD 50 ) and concentration gradient pre-experiments (the concentrations of NiCl 2 solution were set at 8, 10, and 12 mg/kg; the concentrations of Mel solution were set at 2, 5, and 8 mg/kg) to determine the lowest concentration of NiCl 2 that could cause damage in mice and the maximum concentration of Mel that could treat for Ni without causing damage. All animals had free access to food and water for 21 days, and mice were then placed in clean containers and euthanized by slow infusion of carbon dioxide (CO 2 ).…”
Section: Introductionmentioning
confidence: 99%
“… Ijomone et al (2018b) 8 Impact of exposure to waterborne NiCl 2 concentrations (75 and 150 μg/L).on neurobehavioral performances of rats Rat brain Adverse motor activities; negative geotaxis, grooming, grip strength and body rotation Significant elevation in RONS, LPO, MPO, NO, IL-1β and TNF-α levels in cerebrum and cerebellum of treated rats Adedara et al (2020) 9 Effects of Ni exposure through drinking water (10 mg/L, 12 weeks) on neurobehavioral performances and dendrite complexity Male mice Learning and memory impairment in mice, and reduction of dendrite complexity in mouse hippocampi Reduction of histone acetylation (especially at H3K9) and downregulation of H3K9-modulated gene expression Zhou et al (2021) 10 Nickel-induced neurobehavioral alterations in male and female rats after NiCl 2 treatment (1 mg/kg for 60 days) Male and female rats Increased anxiety-like and depression-like behaviour in rats. Cognitive behaviour on the Morris water maze resulted compromised LPO and NO formation with a decrease in SOD and CAT activities Lamtai et al (2020) 11 Neuroprotective potential of melatonin on Ni-induced neurobehavioral alterations in male and female rats C. elegans Functional changes in locomotion and basal slowing response Increasing degeneration of cholinergic, dopaminergic and GABAergic neurons Ijomone et al (2020b) 12 Effects of Ni 2+ on neurotoxic outcomes PC12 cells Changes in oxidative-stress-related gene expression Downregulation of GST Slotkin and Seidler (2010) 13 Effects of nickel concentration (10 μM) on the expression of specific neuronal differentiation markers NT2 cells Nickel may increase the susceptibility to neuro-psychopathology Activation of Akt/PKB kinase pathway and increase of HIF-1a expression. Increased expression of differentiation markers MAP2 and NCAM Ceci et al (2015) 14 Activity of HO measured in tissues of rats after NiCl 2 administration Rat tissue HO activity increased in liver, lung and brain at 17 hr after the NiCl 2 injection Time course, dose-effect, organ selectivity, and species susceptibility relationships for Ni induction of HO activity …”
Section: Resultsmentioning
confidence: 99%
“…These findings were comparable to previous reports on the association of Ni exposure with memory retention and increased the escape latency using the Morris water maze (MWM) ( Kahloula et al, 2014 , He et.al, 2013 ). Specifically, nickel increases the hippocampal level of thiobarbituric acid reactive substances (TBARS) (markers of LPO), and decrease SOD and CAT activities which may culminate in increased anxiety-like and depression-like behaviour in rats ( Lamtai et al, 2020 ). This last study performed histopathological analyses of CA3 pyramidal neurons observing neuronal loss, cellular disorganization, and shrinkage in nickel treated rats of both genders compared to their normal controls ( Lamtai et al, 2020 , El Brouzi et al, 2021 ) demonstrated that intracerebral injection of NiCl 2 at the right hippocampus of the male Wistar rat causes anxiety and depression disorders and lead to cognitive impairment, and again the mechanism was the increase in LPO and NO levels accompanied by a significant decrease in SOD and CAT activities in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations